A Multifunctional Photoswitch: 6π Electrocyclization versus ESIPT and Metalation. Issue 38 (5th August 2014) - Guérin, Juliette; Léaustic, Anne; Delbaere, Stéphanie; Berthet, Jérôme; Guillot, Régis; Ruckebusch, Cyril; Métivier, Rémi; Nakatani, Keitaro; Orio, Maylis; Sliwa, Michel; Yu, Pei
Abstract A terthiazole‐based molecular switch associating 6π electrocyclization, excited state intramolecular proton transfer (ESIPT), and strong metal binding capability was prepared. The photochemical and photophysical properties of this molecule and of the corresponding nickel and copper complexes were thoroughly investigated by steady‐state and ultrafast absorption spectroscopy and rationalized by DFT/TDDFT calculations. The switch behaves as a biphotochrome with time‐dependent photochemical outcome and displays efficient ESIPT‐based fluorescence photoswitching. Both photochemical reactions are suppressed by nickel or copper metalation, and the main factors contributing to the quenching of the electrocyclization are discussed.